2011
DOI: 10.1209/0295-5075/95/43001
|View full text |Cite
|
Sign up to set email alerts
|

Minimal parameter implicit solvent model for ab initio electronic-structure calculations

Abstract: We present an implicit solvent model for ab initio electronic structure calculations which is fully self-consistent and is based on direct solution of the nonhomogeneous Poisson equation. The solute cavity is naturally defined in terms of an isosurface of the electronic density according to the formula of Fattebert and Gygi (J. Comp. Chem. 23, 6 (2002)). While this model depends on only two parameters, we demonstrate that by using appropriate boundary conditions and dispersionrepulsion contributions, solvation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(146 citation statements)
references
References 23 publications
1
144
1
Order By: Relevance
“…For the TDDFT calculation, an effective system of nile red together with an extended solvation shell is cut out of the much larger classical MD periodic box, where the extent of the solvation shell is defined through a cutoff radius R shell centered on all heavy atoms in nile red and solvent molecules are retained for the TDDFT system if their centre of mass lies within the volume V (R shell ) defined by the combined volume of the spheres on all heavy atoms. To avoid a spurious closure of the band gap [49] and reduce spurious charge transfer states in polar solvents that have been reported for both (semi)-local and hybrid exchange-correlation functionals [9,11], the entire TDDFT system containing the solute and the explicit solvation shell is placed in an implicit solvent model [50] with 0 set to the relative static permittivity of the solvent in question. This guarantees that the explicit solvent molecules on the edge of the explicit solvent volume are correctly screened and the long range continuum effects of the solvent are accounted for.…”
Section: B Colour Predictionmentioning
confidence: 99%
“…For the TDDFT calculation, an effective system of nile red together with an extended solvation shell is cut out of the much larger classical MD periodic box, where the extent of the solvation shell is defined through a cutoff radius R shell centered on all heavy atoms in nile red and solvent molecules are retained for the TDDFT system if their centre of mass lies within the volume V (R shell ) defined by the combined volume of the spheres on all heavy atoms. To avoid a spurious closure of the band gap [49] and reduce spurious charge transfer states in polar solvents that have been reported for both (semi)-local and hybrid exchange-correlation functionals [9,11], the entire TDDFT system containing the solute and the explicit solvation shell is placed in an implicit solvent model [50] with 0 set to the relative static permittivity of the solvent in question. This guarantees that the explicit solvent molecules on the edge of the explicit solvent volume are correctly screened and the long range continuum effects of the solvent are accounted for.…”
Section: B Colour Predictionmentioning
confidence: 99%
“…These systems are: a fragment of the L99A/M102Q mutant of the T4 lysozyme protein, 61,62 and a nanocrystal of gallium arsenide in the wurtzite structure, with hydrogen termination. 63 Figure 7 illustrates these systems.…”
Section: Large Systems and Computational Overheadmentioning
confidence: 99%
“…Absorption spectra of IRDye QC-1, IRDye 800CW and Cy5.5 in isolation were calculated using an implicit solvation model with a relative dielectric constant of 80 in order to account for the screening of the aqueous environment. 40 The two models of the stacked dye-quencher systems for a nucleotide separation of zero were obtained by taking the optimized isolated structures of IRDye QC-1, as well as IRDye 800CW and Cy5.5, and placing the dye on top of the quencher in a flat stacking, such that the alignment of the dipole moments of the dominant excitations in the individual systems is maximized. It was found that the closest stacking expected to maximize the excitonic coupling between the dye and the quencher and thus the largest changes in the absorption spectra can be achieved by rotating the quencher by 180 degrees with respect to the dye system.…”
Section: Time-dependent Density Functional Theory (Tddft) Calculationsmentioning
confidence: 99%